2014
DOI: 10.1016/j.placenta.2014.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Placental pathologic changes of maternal vascular underperfusion in bronchopulmonary dysplasia and pulmonary hypertension

Abstract: Introduction Bronchopulmonary dysplasia (BPD) is the most common chronic lung disease of infancy, and BPD-associated pulmonary hypertension (PH) is a serious complication that can negatively impact later childhood health. There is growing evidence that lung injury leading to BPD and PH is due to chronic fetal hypoxia-ischemia. The purpose of this study was to investigate whether placental pathologic changes of maternal vascular underperfusion (MVU) are associated with BPD, and further increased with PH. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 23 publications
4
93
2
2
Order By: Relevance
“…10 Placenta acts as the director of the whole fetal development and its pathology has already been associated with lung and vascular disease in the offspring: Mestan et al have shown that maternal placental vascular underperfusion is associated with the development of BPD among preterm infants. 11 Fetal Doppler examination enables clinicians to identify placental underperfusion and the resulting adverse fetal environment. Experimental sheep FGR models have highlighted impaired lung function and structure as well as endothelial dysfunction in growth-restricted offspring suggesting that placental insufficiency may impair both pulmonary angiogenesis and alveolarisation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Placenta acts as the director of the whole fetal development and its pathology has already been associated with lung and vascular disease in the offspring: Mestan et al have shown that maternal placental vascular underperfusion is associated with the development of BPD among preterm infants. 11 Fetal Doppler examination enables clinicians to identify placental underperfusion and the resulting adverse fetal environment. Experimental sheep FGR models have highlighted impaired lung function and structure as well as endothelial dysfunction in growth-restricted offspring suggesting that placental insufficiency may impair both pulmonary angiogenesis and alveolarisation.…”
Section: Discussionmentioning
confidence: 99%
“…Data about prenatal and neonatal characteristics were prospectively collected in the obstetric medical record and Neonatal Unit database, respectively. FGR diagnosis was based on the coexistence of failing fetal growth in utero, defined as the reduction of the estimated fetal weight of at least 1 SD in two ultrasound scans within 2 weeks and fetal Doppler velocimetry abnormalities, defined as the presence of one of the following conditions: 11 ► umbilical artery pulsatility index (PI) greater than the 95th centile, ► absent or reversed end diastolic flow velocities on at least 50% of the Doppler waveforms from the umbilical artery on at least one occasion during pregnancy, ► cerebral redistribution, defined as occurring when both the umbilical artery PI is greater than the 95th centile and the middle cerebral artery PI is less than the 5th centile for GA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Recently, there have been some reports that placental pathologic changes of maternal vascular underperfusion in BPD are associated with increased risk of pulmonary hyper tension, 29 and after a systematic review and metaanalysis, oligohydramnios and SGA were shown as significant risk fac tors of pulmonary hypertension in infants with BPD. 30 Addi tionally, in our study, SGAP was a significant risk factor of pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Although PH predominantly develops in the very low birth weight and very preterm infant, some infants develop late onset PH after a couple of weeks 22 36 37. Furthermore, the moderate but growth-retarded preterm infant has been shown to develop PH in a considerable number of cases 36.…”
Section: Background On Ph In the Neonate And Infantmentioning
confidence: 99%